Radar based sensing for healthcare monitoring - Chen, Evelyn Meiying. (2011)
Continuous-Wave (CW) Doppler radar was deployed as the main subject in this case study. As shown in the recent advancement in technologies for signal processing, it can be seen that this technique is able to detect the movement of the whole body. For example in this case study, the focus will be on the detection for individual heartbeats rate. In addition, the radar based sensing will research on the distance which is the limitation of the well proven technology such as the ECG. In this case study, a CW Doppler radar prototype was developed and ready for experimental test to evaluate on the results obtained. The author will address the various methods that will be used to capture the data using the CW Doppler radar. There are numerous methods to be deployed but in this case study; the methods selected for the extraction of data are the small angle approximation phase demodulation, the spectral estimation and the pruning of result. As mentioned above, the three methods algorithms will be written in MATLAB code as it is chosen as the software to run the simulation. The results of this case study will be based on these two requirements, the position of the subjects’ as well as the distance apart from the antenna to the subject’s chest level. Observation showed that the signals will fade at a longer distance regardless of the directions. In the overall conclusion, the author indicates that both the distance and the position play vital role in the measurement of the heartbeat.